Integrated water and power modeling framework for renewable energy integration - Dozier, André, author; Labadie, John W., advisor; Zimmerle, Dan, committee member; Salas, Jose, committee member (Colorado State University. Libraries, 2012)
Increasing penetration of intermittent renewable energy sources into the bulk electricity system has caused new operational challenges requiring large ramping rate and reserve capacity as well as increased transmission congestion due to unscheduled flow. Contemporary literature and recent renewable energy integration studies indicate that more realism needs to be incorporated into renewable energy studies. Many detailed water and power models have been developed in their respective fields, but no free-of-charge integrated water and power system model that considers constraints and objectives in both systems jointly has been constructed. Therefore, an integrated water and power model structure that addresses some contemporary challenges is formulated as a long-term goal, but only a small portion of the model structure is actually implemented as software. A water network model called MODSIM is adapted using a conditional gradient method to be able to connect to an overarching optimization routine that decomposes the water and power problems. The water network model is connected to a simple power dispatch model that uses a linear programming approach to dispatch hydropower resources to mitigate power flows across a transmission line. The power dispatch model first decides optimal power injections from each of the hydropower reservoirs, which are then used as hydropower targets for the water network model to achieve. Any unsatisfied power demand or congested transmission line is assumed to be met by imported power. A case study was performed on the Mid-Columbia River in the U.S. to test the capabilities of the integrated water and power model. Results indicate that hydropower resources can accommodate transmission congestion and energy capacity on wind production up until a particular threshold on the penetration level, after which hydropower resources provide no added benefit to the system. Effects of operational decisions to mitigate wind power penetration level and transmission capacity on simulated total dissolved gases were negligible. Finally, future work on the integrated water and power model is discussed along with expected results from the fully implemented model and its potential applications.
Keywords: optimization; water; systems; power; modeling; operations